APPLICATION OF ZEOLITE IN ANIMAL HUSBANDRY - Pollung Siagian (Institut Teknologi Bandung, 2005)
Zeolite used in so various area and inclusive of livestock. The using of zeolite is related to zeolite characteristic as molecule absorber and cation exchange capacity. In return for cation, because metallic binding which owning is easy to release and also easily replace by cation of other. Zeolite ability as molecule absorber caused by its structure is hollow where other molecule that selectively can dissociate molecule which size measure is bigger can fill the cavity. Nature zeolite ability causes it a lot of used for the good livestock area as part of feed and as media of plant for livestock feed and also to improve environmental quality of farm. Zeolite use in research of various livestock type show livestock appearance repair improvement and low feed price. Zeolite use to improve environmental quality also show real result through rate reduction irrigate dirt, dirty air and dirt ammonia rate degradation in cage and also lessen aroma coming from ammonia (NH3) and sulphide hydrogen (H2S) as ferment micro organism result in feces.